2013
DOI: 10.3791/50440
|View full text |Cite
|
Sign up to set email alerts
|

A Laser-induced Mouse Model of Chronic Ocular Hypertension to Characterize Visual Defects

Abstract: Glaucoma, frequently associated with elevated intraocular pressure (IOP), is one of the leading causes of blindness. We sought to establish a mouse model of ocular hypertension to mimic human high-tension glaucoma. Here laser illumination is applied to the corneal limbus to photocoagulate the aqueous outflow, inducing angle closure. The changes of IOP are monitored using a rebound tonometer before and after the laser treatment. An optomotor behavioral test is used to measure corresponding changes in visual cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The procedure of laser illumination has been described previously. 17,18 In brief, 2-to 3-month-old mice were anesthetized by an intraperitoneal injection of ketamine (100 mg/kg; Butler Schein Animal Health, Dublin, OH, USA) and xylazine (10 mg/kg; Lloyd, Inc., Iowa, Shenandoah, IA, USA). Approximately 80 to 100 laser spots (514-nm wavelength and 200-lm diameter, Ultima 2000 SE; Coherent, Inc., Santa Clara, CA, USA) were applied to the corneal limbus of the right eye.…”
Section: Induction Of Iop Elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure of laser illumination has been described previously. 17,18 In brief, 2-to 3-month-old mice were anesthetized by an intraperitoneal injection of ketamine (100 mg/kg; Butler Schein Animal Health, Dublin, OH, USA) and xylazine (10 mg/kg; Lloyd, Inc., Iowa, Shenandoah, IA, USA). Approximately 80 to 100 laser spots (514-nm wavelength and 200-lm diameter, Ultima 2000 SE; Coherent, Inc., Santa Clara, CA, USA) were applied to the corneal limbus of the right eye.…”
Section: Induction Of Iop Elevationmentioning
confidence: 99%
“…Approximately 80 to 100 laser spots (514-nm wavelength and 200-lm diameter, Ultima 2000 SE; Coherent, Inc., Santa Clara, CA, USA) were applied to the corneal limbus of the right eye. 17,18 To achieve the long-term ocular hypertension (>10 weeks), we combined laser photocoagulation with microbead injection. One microliter of polystyrene microbeads (10-lm diameter, 14.4 3 10 6 beads/ mL in PBS; Life Technologies, Eugene, OR, USA) was immediately injected into the anterior chamber of the same eye by a Hamilton syringe right after laser illumination.…”
Section: Induction Of Iop Elevationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, using the aforementioned behavioral techniques in rodent models that display disease etiology that is similar to humans, such as the DBA/2 mouse, allows us to conduct studies that obtain valuable information on disease mechanisms and therapeutic strategies at considerably lower cost with more data points. We can use these techniques in mice to evaluate therapeutic intervention in rodent models of disease (Adamus et al, 2012; Cahill et al, 2011; Krempler et al, 2011; Savigni et al, 2013), and RGC axon regeneration (de Lima et al, 2012), test variables such as age and gender (van Alphen et al, 2009), neuronal and RGC disease mechanisms in glaucomatous mice (Burroughs et al, 2011; Feng et al, 2013; Kaja et al, 2011), similar to the assessment of visual deficits in other animal models of disease (Pinto et al, 2007; Pinto et al, 2005; Puk et al, 2009; Richards et al, 2008; Roeser and Baier, 2003; Schmucker and Schaeffel, 2006; Umino and Solessio, 2013). Such data contribute to the pre-clinical development of promising therapeutic interventions prior to human clinical trials and benefit from their non-invasive and comprehensive nature resembling many of the aspects of human clinical trials.…”
Section: Clinical Relevance Of Data Derived From Behavioral Assaysmentioning
confidence: 99%
“…By now, IOP reduction is the only treatment strategy for all types of glaucoma. 4 In order to investigate the neuropathologic mechanism of glaucoma and develop effective therapeutic interventions, many kinds of experimental glaucoma models were formed by elevating IOP or changing gene MYOC or a1 subunit of collagen type 1 in rats, 6,7 mice, 8,9 monkeys, 10,11 dogs, 12 cats, 12 and several other species. 12 Studies based on these animal models have shown that neuropathology is related with deprivation of target neurotrophic factor, 13,14 oxidative stress, 15,16 mitochondrial dysfunction, 17 excitotoxic damage, [18][19][20] and inflammation, 21 activation of apoptotic signals, 22,23 ischemia.…”
Section: Introductionmentioning
confidence: 99%